Effects of plant active substances in rheumatoid arthritis—a systematic review and network meta-analysis - Peng, Qiuwei; Wang, Jian; Li, Kesong; Xia, Congming; Yao, Chuanhui; Guo, Qiuyan; Gong, Xun; Tang, Xiaopo; Jiang, Quan (Frontiers in Pharmacology, 2025)
BackgroundPlant active substances are extensively utilized in treating rheumatoid arthritis (RA). Despite numerous experimental and clinical studies on plant active substances their efficacy remains largely unsubstantiated. The widespread use of these extracts as therapeutic measures for RA is problematic due to the lack of compelling evidence.ObjectiveOur research aims to assess the impact of plant active substances on RA by conducting a network meta-analysis.MethodsWe systematically searched four electronic databases—PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, and Web of Science—from their inception to August 2024. The main focus was on assessing primary outcomes, including the Visual Analogue Scale (VAS), inflammatory markers, Swollen Joint Count (SJC), Tender Joint Count (TJC), and Disease Activity Score on 28 joints (DAS28). We performed data analysis using StataMP 15.1 software and ranked the therapeutic effects based on the Surface Under the Cumulative Ranking Curve (SUCRA) probability values.ResultsBased on screening procedures, 18 eligible studies were incorporated into the analysis. These studies encompassed a total of 1,674 RA patients and investigated 10 different plant active substance therapies. Specifically, 10 studies included VAS indicators, 17 studies included inflammatory marker indicators, 14 studies included DAS28 indicators, 13 studies included SJC indicators, and 13 studies included TJC indicators. Based on SUCRA values, quercetin appeared to be the most effective treatment for decreasing serum VAS levels (67.3%). Furthermore, curcumin emerged as the most promising option for reducing inflammatory marker levels (72.3%), SJC (75.6%), and TJC (76.2%). Lastly, with respect to DAS28, resveratrol emerged as the optimal choice (74.3%).ConclusionAccording to the network meta-analysis (NMA), curcumin exhibited superior efficacy compared to placebo in decreasing SJC and TJC. Additionally, curcumin demonstrated greater effectiveness in reducing inflammatory markers. Quercetin was more effective in reducing VAS, and resveratrol was more effective in reducing DAS28. Patients with RA may benefit from these findings. Insightful information from this study is helpful for RA patients to consider using plant active substance therapies. For their efficacy and safety to be confirmed, more proof is needed.